Characterisation of the Fusarium graminearum-Wheat Floral Interaction. (4th October 2011) - Brown, Neil A.; Bass, Chris; Baldwin, Thomas K.; Chen, Huaigu; Massot, Fabien; Carion, Pierre W. C.; Urban, Martin; van de Meene, Allison M. L.; Hammond-Kosack, Kim E.
Abstract : Fusarium Ear Blight is a destructive fungal disease of cereals including wheat and can contaminate the crop with various trichothecene mycotoxins. This investigation has produced a new β -glucuronidase (GUS) reporter strain that facilitates the quick and easy assessment of plant infection. The constitutively expressed gpdA:GUS strain of Fusarium graminearum was used to quantify the overall colonisation pattern. Histochemical and biochemical approaches confirmed, in susceptible wheat ear infections, the presence of a substantial phase of symptomless fungal growth. Separate analyses demonstrated that there was a reduction in the quantity of physiologically active hyphae as the wheat ear infection proceeded. A simplified linear system of rachis infection was then utilised to evaluate the expression of several TRI genes by RT-qPCR. Fungal gene expression at the advancing front of symptomless infection was compared with the origin of infection in the rachis. This revealed that TRI gene expression was maximal at the advancing front and supports the hypothesis that the mycotoxin deoxynivalenol plays a role in inhibiting plant defences in advance of the invading intercellular hyphae. This study has also demonstrated that there are transcriptional differences between the various phases of fungal infection and that these differences are maintained as the infection proceeds.